Safety biomarkers for development of vaccines and biologics: Report from the safety biomarkers symposium held on November 28–29, 2017, Marcy l'Etoile, France. Issue 51 (3rd December 2020) - Doubovetzky, Michel; Ataman-Önal, Yasemin; Chousterman, Benjamin; Feroldi, Emmanuel; Garçon, Nathalie; Grillet, Marie-Hélène; Kramer, Daniel; Laurent, Sébastien; Lewis, David J.M.; Luna, Ernesto; Manigold, Tobias; Syntin, Patrick; et al.
Abstract: Vaccines prevent infectious diseases, but vaccination is not without risk and adverse events are reported although they are more commonly reported for biologicals than for vaccines. Vaccines and biologicals must undergo vigorous assessment before and after licensure to minimise safety concerns. Potential safety concerns should be identified as early as possible during the development for vaccines and biologicals to minimize investment risk. State-of-the art tools and methods to identify safety concerns and biomarkers that are predictive of clinical outcomes are indispensable. For vaccines and adjuvant formulations, systems biology approaches, supported by single-cell microfluidics applied to translational studies between preclinical and clinical studies, could improve reactogenicity and safety predictions. Next-generation animal models for clinical assessment of injection-site reactions with greater relevance for target human population and criteria to define the level of acceptability of local reactogenicity at vaccine injection sites in pre-clinical animal species should be assessed. Advanced in silico machine-learning-based analytics, species-specific cell or tissue expression, receptor occupancy and kinetics and cell-based assays for functional activity are needed to improve pre-clinical safety assessment of biologicals. The in vitro MIMIC® system could be used to compliment preclinical and clinical studies for assessing immune-toxicity, immunogenicity, immuno-inflammatory and mode of action of biologicals and vaccines. Sanofi Pasteur brought together leading experts in this field to review the state-of-the-art at a unique 'Safety Biomarkers Symposium' on 28–29 November 2017. Here we summarise the proceedings of this symposium. This unique scientific meeting confirmed the importance for institutions and industrial organizations to collaborate to develop tools and methods needed for predicting reactogenicity and immune-inflammatory reactions to vaccines and biologicals, and to develop more accuracy, reliability safety biomarkers, to inform decisions on the attrition or advancement of vaccines and biologicals.